2022
DOI: 10.24251/hicss.2022.629
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmically Controlled Automated Decision-Making and Societal Acceptability: Does Algorithm Type Matter?

Abstract: As technological capabilities expand, an increasing number of decision-making processes (e.g., rankings, selections, exclusions) are being delegated to computerized systems. In this paper, we examine the societal acceptability of a consequential decisionmaking system (university admission) to those subject to the decision (i.e., applicants). We analyze two key drivers: the nature of the decision-making agent (a human vs an algorithm) and the decision-making logic used by the agents (predetermined vs emerging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Within the algorithm factors category, one was the anthropomorphic presentation of an algorithm, along with its complexity, understandability, accuracy, and ability to learn. Similarly, Grange [41] indicated the use of machine learning or "black-box" techniques as a tool to automate decisions. Because humans may be unaware of how algorithms are designed to operate, it is critical that the perceptions of those impacted by algorithmic-based decisions are taken on board throughout the design, implementation, and review processes.…”
Section: Agency and Decision-making Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the algorithm factors category, one was the anthropomorphic presentation of an algorithm, along with its complexity, understandability, accuracy, and ability to learn. Similarly, Grange [41] indicated the use of machine learning or "black-box" techniques as a tool to automate decisions. Because humans may be unaware of how algorithms are designed to operate, it is critical that the perceptions of those impacted by algorithmic-based decisions are taken on board throughout the design, implementation, and review processes.…”
Section: Agency and Decision-making Algorithmsmentioning
confidence: 99%
“…This was related to the app not working as perceived by the Twitter user. This indicated that the app was perceived as having the capacity to think or act autonomously, leading to the opposition of system use [40,41,88].…”
Section: Functioningmentioning
confidence: 99%